Earnings Announcements and Information Asymmetry: An Intra-Day Analysis - LIBBY, THERESA; MATHIEU, ROBERT; ROBB, SEAN W. G. (Contemporary Accounting Research, 2002)
This paper examines the effect of earnings announcements on information asymmetry as perceived by specialists. We use changes in quoted bid-ask spreads and depths (relative to the average value in the non-announcement period) as proxies for changes in information asymmetry in the market. To our knowledge, we are the first to employ a model that captures the simultaneous nature of the specialists' choice of spreads and depths in reaction to earnings news. We provide evidence that spreads are wider and depths are smaller before the release of earnings announcements. We also find that changes to depths are greater for announcements of quarterly earnings than for announcements of annual earnings and changes to spreads persist longer into the post-announcement period when announcements are made outside trading hours. These changes to spreads and depths persist when earnings announcements are made after trading hours.